Late Cenozoic Glaciations in Patagonia and Tierra del Fuego: an up-dated review - Rabassa, Jorge Oscar (2011)
The Patagonian glaciations developed from the latest Miocene (c. 6 Ma) in multiple events of varied duration and intensity. Most of the present glacial landscape is the result of the glacial modelling during the Pleistocene, since the Great Patagonian Glaciation (GPG; c. 1 Ma). The Patagonian Andes were covered by a continuous mountain ice sheet, from 37°S to Cape Horn (56°S), in at least five major glaciations over more than 15 cold events over the last million years. Before GPG, the glaciers were restricted to isolated ice caps along the mountain ranges. The present drainage network was developed after the Last Glacial Maximum [LGM; c. 25 calibrated kiloyears before present (cal. ka bp)], particularly those cases with drainage reversal, when the glaciers began to melt as a result of global climatic changes. The environmental impact of glaciations extended not only all over Patagonia, but to the Pampas as well.